2018
DOI: 10.1080/17435390.2018.1425500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the proteome and lipidome profiles of human lung cells after low dose and chronic exposure to multiwalled carbon nanotubes

Abstract: 2018) Characterization of the proteome and lipidome profiles of human lung cells after low dose and chronic exposure to multiwalled carbon nanotubes, Nanotoxicology, 12:2, 138-152,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Critically short telomers result in activation of DNA damage response proteins, such as the phosphorylated forms of ataxia telangiectasia mutated (ATM), H2A histone family member X (H2A.X), and RAD17 checkpoint clamp loader component (RAD17) [ 34 ]. While many studies have shown that exposure to MWCNT leads to increased levels of DNA strand breaks and increased DNA repair activity and DNA damage [ 9 , 19 , 25 ], other studies did not observe genotoxicity following MWCNT-exposure [ 5 , 35 , 36 ]. In this study, we did not observe a regulation of genes involved in DNA damage or repair (i.e., ATM , ATR , RAD17 , NIEL3 , XPA , ALKBH1 , ALKBH5 , or OGG1 ) in HBEC-3KT cells exposed to NM-401.…”
Section: Discussionmentioning
confidence: 99%
“…Critically short telomers result in activation of DNA damage response proteins, such as the phosphorylated forms of ataxia telangiectasia mutated (ATM), H2A histone family member X (H2A.X), and RAD17 checkpoint clamp loader component (RAD17) [ 34 ]. While many studies have shown that exposure to MWCNT leads to increased levels of DNA strand breaks and increased DNA repair activity and DNA damage [ 9 , 19 , 25 ], other studies did not observe genotoxicity following MWCNT-exposure [ 5 , 35 , 36 ]. In this study, we did not observe a regulation of genes involved in DNA damage or repair (i.e., ATM , ATR , RAD17 , NIEL3 , XPA , ALKBH1 , ALKBH5 , or OGG1 ) in HBEC-3KT cells exposed to NM-401.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are mostly related to processes such as cellular proliferation, immune response, inflammation, amino acid‐dependent cell signaling, and secretion of organic electrolytes. For example, pathway analysis revealed perturbations in aminoacyl‐t‐RNA biosynthesis, further suggesting that there is a significant change in amino acid and protein metabolism (Phuyal et al, 2018). In agreement with these findings, effects of MWCNTs evidenced by other research also indicate similar cellular processes and responses related to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As such, biocompatible NPs should not disrupt lipid homeostasis. For example, CNTs have been shown to induce lipid accumulation in different models, which could be related with the toxic effects of CNTs (Phuyal et al, 2018; H. Yang et al, 2019; T. Yang et al, 2020; H.‐Y. Zhang, Chen, Shao, Wang, & Liu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies also suggested a role of ECs in lipid metabolism that disturbance of lipid droplet biogenesis could impair the function of ECs leading to disease development (Jung et al, 2020; Pacia et al, 2020). Interestingly, exposure to NMs disrupted lipid homeostasis in many types of cells, such as neurons (Bramini et al, 2019), bronchial epithelial cells (Phuyal et al, 2018), liver cells (Almansour, Sajti, Melhim, & Jarrar, 2016), vascular smooth muscle cells (H. Yang, Li, Yang, Liu, & Cao, 2019), and macrophages (Luo, Peng, Huang, & Cao, 2020), indicating that changes in lipid profiles are common outcomes following exposure to toxic NMs. But to the best of our knowledge, whether zirconia NPs will alter lipid profiles in ECs has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%